Productivity of new sainfoin varieties and promising lines in the conditions of the south of Russia - A. A. Regidin; S. A. Ignatiev; N. S. Kravchenko; K. N. Goryunov (Зерновое хозяйство России)
The current paper has presented the study results of promising lines of sainfoin in the competitive variety testing. The purpose of the current study was to estimate the fodder, seed productivity and quality of the fodder mass of promising sainfoin lines for the introduction of the best of them into production and use in breeding. The study was carried out in the fields of the FSBSI “ARC “Donskoy”. The objects of study were nine sainfoin varieties and promising lines. The standard was a sainfoin variety ‘Veles’. According to the study results, green mass productivity of the lines ‘Sin 2/2010’, ‘Sin 4/2010’ and ‘Sin 8/95’ was 30.1 t/ha, 30.1 t/ha and 30.3 t/ha, or on 7.9 % and 8.6 % higher than that of the standard variety ‘Veles’ (27.9 t/ha). On average, for 2 cycles, the seed productivity of the studied lines varied from 0.93 t/ha to 1.02 t/ha and was significantly higher than that of the standard variety (0.85 t/ha). On average, during two cycles, the lines ‘Sin 3/2010’ and ‘Sin 3/2004’ produced the largest seed yield (1.02 t/ha). The lines ‘Sin 13/93’ and ‘Sin 4/2010’, respectively, exceeded dry matter yield of the standard variety ‘Veles’ on 9.8% and 10.0%, and feed units per 1 ha on 14.6% and 14.8%. The lines ‘Sin 3/2010’, ‘Sin 3/2004’ and ‘Sin 13/93’ are going to be propagated in isolated plots for further study under production conditions